Ex Ante Evaluation Of The Liability Company Policy Of State-Owned Enterprises (Soe) Jasa Tirta Ii In The Aspect Of Public Services Using The Cost Benefit Analysis (CBA) Method - Wulandari, Ervina; Rahmatunnisa, Mudiyati; Karlina, Nina (UNIVERSITAS PAKUAN, 2024)
The changes in the global economy and competitive business growth demand increased efficiency, effectiveness, and professionalism in all business lines of SOEs, including Jasa Tirta II. In order to realize this, the Ministry of SOEs conducts SOE development, namely business model restructuring, including the stipulation of Government Regulation Number 113 of 2021 concerning Amendments to Government Regulation Number 25 of 1976 concerning State Capital Participation of the Republic of Indonesia for the Establishment of the Company (Persero)